x-1=6,x=

Simple and best practice solution for x-1=6,x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-1=6,x= equation:



x-1=6.x=
We move all terms to the left:
x-1-(6.x)=0
We add all the numbers together, and all the variables
x-(+6.x)-1=0
We get rid of parentheses
x-6.x-1=0
We add all the numbers together, and all the variables
-5x-1=0
We move all terms containing x to the left, all other terms to the right
-5x=1
x=1/-5
x=-1/5

See similar equations:

| -8n-(n+6)=-5n+26 | | y−3/2=2 | | 2x+5-5=x+3-5 | | x-2=-10,x= | | 10=2(s+4) | | 2(4-3n)=-5n | | 8−n=5 | | 1+2m-+2=3+m | | f−2/2=2 | | (w+8)=w | | p−3/2=2 | | -3x-2=7(2x+7) | | 24=4x+8,x= | | 5x+2+5x-8=74 | | 24=4x+8x= | | x+2=10,x= | | 4-p=1 | | 6x+10=-4(x-5) | | 4x+5+5x-7=79 | | 3x-5-2x=-4 | | r+15=4r−6 | | 14+2p=-6(1-2p) | | x+5=3/4 | | 3(p−4)=9 | | 4/3x=-2/3 | | 4x+6=8x-8 | | 28=0.57x | | 11^-9x=15^-x-5 | | 173=89-v | | 8q^2-3q=7q^2-5q+48 | | u-0.75=2.6 | | 2x+2(x12)=56 |

Equations solver categories